Serum Fatty Acid Synthase Level in Patients with Prostate Cancer and Benign Prostatic Hyperplasia - Farooq Yaseen Khuhair1, Hassan H. AL-Saeed1, Laith Amer Abd-Al-Hussain2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Human Fatty Acid Synthase is highly expressed in many human cancers. Previous studies have shown that this enzyme is expressed at very high levels in prostate cancer and that the growth of prostate cancer cell line can be inhibited by pharmacological inhibitors that target this enzyme. Additionally, some studies have reported that this enzyme is overexpressed not only in tissue, but also in serum of patients with various cancers. The aim of this study was to,evaluate serum levels of this enzyme in patients with prostate cancer and in patients with benign prostatic hyperplasia as well as to investigate whether it can be used as a biomarker for detection of prostate cancer and benign prostatic hyperplasia. Methods: By using an FASN ELISA kit, we measured serum levels of Human Fatty Acid Synthase in 35 patients with prostate cancer and 35 patients with benign prostatic hyperplasia. We also measured serum FASN levels of 35 healthy volunteers enlisted as normal controls. Results: Serum FASN levels in prostate cancer patients were significantly higher than in healthy control subjects, but FASN levels in patients with benign prostatic hyperplasia were not significantly higher than in healthy control subjects. Conclusions: Serum FASN levels are expressed at significantly high levels in human prostate cancer. Serum FASN levels were not expressed at significantly high levels in human benign prostatic hyperplasia. FASN serum levels may be additional biomarker for prostate cancer detection.